Clinical and economic assessment of nosocomial pneumonia antibacterial therapy in Moscow hospital - D. D. Ivanova; I. N. Sychev; N. B. Lazareva (Фармакоэкономика)
Objective: to conduct clinical and economic analysis of nosocomial pneumonia antibacterial therapy in a multidisciplinary hospital in Moscow.Material and methods. The medical records of patients admitted to Yudin City Clinical Hospital in Moscow in 2019–2021 were analyzed retrospectively. Pharmacoepidemiological analysis included the structure of prescriptions of antibacterial drugs (ABDs), features of empirical and etiotropic therapy, duration of using ABDa and other parameters. In total, 110 cases of severe nosocomial pneumonia caused by ESKAPE pathogens were selected for analysis. Direct medical costs and cost-effectiveness coefficients were calculated based on real world data.Results. It was established that nosocomial pneumonia is the most common complication among hospitalized patients in the intensive care unit (ICU). The etiology of nosocomial pneumonia was mostly presented by K. pneumoniae, A. Baumanii, and P. aeruginosa. The administered ABDs included 31 international nonproprietary names of the group J01 Systemic antibacterial drugs. The direct medical costs of empirical antibacterial therapy averaged for 9367 rubles (2118 rubles [1462; 3525]). Comparative cost-effectiveness analysis was performed based on surrogate and endpoints. It was found that direct medical costs associated with ESKAPE pathogens spend about 70% of the budget of established tariff to pay for medical care of the compulsory health insurance program for the patient's stay in the ICU.Conclusion. Antibacterial therapy costs for nosocomial pneumonia significantly increase the total cost of a patient's hospital stay. Сlinical and economic assessment of drug use help optimize therapy costs and develop a hospital formulary of antimicrobial drugs.